Preparation method and application of lignin-based resin and carbon material for battery
By separating lignin from papermaking black liquid, high molecular weight lignin-based resin was prepared, combined with low-temperature pre-carbonization and gas-phase deaeration technology, the problems of poor raw material stability and graphite materials during biomass gasification were solved, and high-performance carbon materials suitable for sodium ion batteries were prepared to meet the electrochemical performance requirements of the battery.
Patent Information
- Application Number
- CN202311226623.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-09-21
AI Technical Summary
In the prior art, there are problems of poor raw material stability, equipment blockage and fluctuations in the composition of synthesis gasification process, resulting in unstable working conditions of the gasifier, and graphite carbon materials have low specific capacity and lithium dendrites in lithium-ion batteries. The electrochemical performance of sodium ion battery electrode materials is not ideal, making it difficult to meet the practical application needs.
The high molecular weight lignin is prepared as a hard carbon precursor by separating lignin from the papermaking black liquid by cross-linking curing, preoxidation, precarbonization and gas-phase deaze-based resin. Combined with low-temperature precarbonization and gas-phase deaze-deaze-producing technology, high-purity and low-ash battery carbon materials are prepared.
The carbon material for batteries prepared has excellent electrochemical properties, with the first Coulomb efficiency of up to 88%, the gram capacity is above 300mAh/g, and the cycle stability is good. It is suitable for sodium ion battery negative electrode materials, with good electrochemical properties and high current charging performance, and is suitable for electric vehicles and energy storage fields.
Smart Images

Figure BDA0004463219520000221 
Figure HDA0004463219650000011 
Figure HDA0004463219650000012
Abstract
Description
Technical Field
[0001] The present application belongs to the field of biomass refining and comprehensive utilization, and specifically relates to a preparation method and application of carbon materials for batteries, and a lignin-based resin. Background Art
[0002] Due to the non-renewable nature of primary energy sources such as coal, oil and natural gas, as well as the greenhouse effect and environmental problems during their use, the clean and environmentally friendly utilization of renewable biomass resources that have both material and energy properties has shown great development potential and has become the focus of research and application.
[0003] my country produces 700 million tons of agricultural straw and 200 million tons of forestry solid waste annually, a considerable portion of which is discarded or burned on site, causing energy waste and environmental pollution. These agricultural and forestry resources biomass can be dried and crushed to produce synthesis gas with H2 and CO as the main components through gasification reaction, which is the main way to achieve clean and environmentally friendly utilization of biomass energy. The synthesis gas obtained after gasification can be purified and converted to synthesize clean fuels and high value-added chemicals through Fischer-Tropsch synthesis technology or other conversion technologies.
[0004] Similar to coal gasification technology, the current biomass gasification mainly uses firewood and straw as the main raw materials. After preliminary crushing to a suitable particle size range, it is transported to the gasifier in the form of block solids (particle size 8-50mm) or solid particles (particle size 4-8mm) through inert gas for gasification reaction.
[0005] High-pressure feeding is a prerequisite for realizing high-pressure gasification technology, which can significantly reduce the volume of the gasifier and the energy consumption of pressurizing the syngas in the downstream process section. For solid biomass gasification raw materials, the pressure of the gas transported in the feed lock hopper needs to be higher than the pressure of the gasifier to achieve high-pressure feeding. This feeding method is relatively cumbersome to operate and has poor stability. Since mechanical valves are used to seal high-pressure gas, long-term high-frequency switching operations are prone to valve failure or damage, causing the gasifier to be forced to shut down due to feed interruption. At the same time, the inert gas used for biomass material transportation is not easy to remove in the downstream process section, which will cause a decrease in the syngas content and system efficiency. On the other hand, the gasifier has high requirements for the stability of the raw materials. Even if the feed amount can be kept stable, changes in the type and composition of the feed biomass will also lead to significant fluctuations in the gasification conditions, gas production and syngas composition. However, the composition of biomass raw materials is complex and changes with type and season, which poses a challenge to the stable regulation of the gasifier working conditions and restricts the maturity and perfection of biomass dry material gasification technology. Therefore, high-pressure feeding of biomass raw materials and the stability of material composition have become important technical issues affecting its resource utilization. In addition, impurities in biomass are prone to scaling during the gasification process and the transportation of gasification products, causing equipment and pipeline blockage.
[0006] Due to the shortage of fossil resources, the development and application of carbon materials have been greatly restricted in recent years. Biomass resources such as forestry biomass and agricultural straw are renewable resources and have become substitutes for fossil resources. Most biomass resources are rich in carbon, so the preparation of various carbon materials using renewable biomass resources as raw materials has always attracted much attention.
[0007] There are many types of carbon materials for batteries, generally including soft carbon, hard carbon, graphite, etc., among which graphite is the most widely used in lithium-ion batteries. However, graphite anodes have problems in application, such as low specific capacity (theoretical specific capacity 372mAh / g), poor low-temperature performance, and easy generation of lithium dendrites on the surface of the anode. In addition, graphite needs to be processed by high-temperature graphitization, which consumes a lot of energy, hindering the development of related battery products.
[0008] Hard carbon refers to carbon that is difficult to graphitize and is a type of amorphous carbon material. Hard carbon has a very high gram capacity for lithium, generally 500 to 1000 mAh / g. Hard carbon has attracted widespread attention due to its low cost, excellent cyclicity and suitability for discharge under high current.
[0009] Sodium-ion batteries are secondary batteries that use the process of sodium ions intercalating and deintercalating between the positive and negative electrodes to achieve charge and discharge. Compared with lithium-ion batteries, sodium-ion batteries have the following advantages: sodium salt raw materials are abundant and inexpensive; due to the characteristics of sodium salts, low-concentration electrolytes can be used to reduce costs; sodium ions do not form alloys with aluminum, and aluminum foil can be used as the negative electrode collector, further reducing costs and weight; due to the sodium-ion battery's no over-discharge characteristics, sodium-ion batteries are allowed to discharge to zero volts. Sodium-ion batteries have a high energy density and obvious cost advantages; however, due to the unsatisfactory electrochemical properties of electrode materials, the development of sodium-ion batteries has been relatively slow, and finding suitable electrode materials is one of the keys to the large-scale practical application of sodium-ion energy storage batteries.
[0010] The atomic radius of sodium ions is larger than that of lithium ions. Due to the small spacing between graphite layers (0.34nm), it is difficult for sodium ions to enter the graphite layer. As a negative electrode material for sodium ion batteries, hard carbon has many advantages over traditional electrode graphite. Hard carbon has a loose, porous and interlaced layered structure, which can store a large amount of sodium ions, but its initial efficiency as a sodium ion negative electrode material is relatively low, and its cycle performance is poor. As in the prior art, CN102701184A discloses a sodium ion battery carbon negative electrode material with a large interlayer spacing, which is obtained by pyrolysis of aromatic organic matter, and the pyrolysis conditions are carbonization at 600-1600°C in an inert atmosphere for 2-24h; the aromatic organic matter is polyphenyl, phenolic acid, furfural, polynaphthalene, polyanthracene, asphalt or their derivatives. By controlling the pyrolysis conditions, the pyrolytic carbon material has a certain carbon interlayer spacing and has good reversible sodium ion deintercalation performance. However, the reversible capacity of the negative electrode material is only 175-260 mAh / g, and its capacity and cycle performance cannot meet the use requirements. Summary of the invention
[0011] In order to solve the problems existing in the above-mentioned prior art, the present application provides a method and application of preparing carbon materials for batteries using papermaking black liquor as raw material. The method of the present application is simple to operate and has low energy consumption. The prepared carbon materials for batteries have excellent electrochemical properties.
[0012] The specific technical solutions of this application are as follows:
[0013] 1. A method for preparing a carbon material for a battery, wherein the preparation method comprises the following steps:
[0014] Separation: separating lignin from papermaking black liquor and drying the lignin;
[0015] Polymerization: Dissolve the dried lignin in an alkaline solution, then add a cross-linking agent to carry out a cross-linking curing reaction to obtain a lignin polymer solid;
[0016] Pre-oxidation: pre-oxidizing the lignin polymer solid to obtain a lignin-based resin;
[0017] Pre-carbonization: pre-carbonizing the lignin-based resin under a protective atmosphere to obtain a carbon material precursor 1;
[0018] Gas phase deashing: in a protective atmosphere and under the action of a halogen compound and / or a halogen element, the carbon material precursor 1 is gas phase deashed to obtain a carbon material precursor 2;
[0019] Calcination: The carbon material precursor is crushed and calcined under a protective atmosphere to obtain a carbon material for a battery.
[0020] 2. The preparation method according to item 1, wherein after the pre-carbonization step and before the gas phase deashing step, a washing and drying step is further included: the carbon material precursor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried;
[0021] Preferably, the pickling is carried out using any one or more acids selected from the following: sulfuric acid, hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, formic acid and acetic acid.
[0022] 3. The preparation method according to item 1 or 2, wherein in the separation step, the papermaking black liquor is acidified with an acidifying agent to separate lignin from the papermaking black liquor; wherein the acidifying agent is selected from any one or more of carbonic acid, sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid;
[0023] More preferably, the acidulant is selected from one, two or three of carbonic acid, sulfuric acid and hydrochloric acid;
[0024] Further preferably, the papermaking black liquor is acidified with carbonic acid to separate the liquid lignin, and then the liquid lignin is acidified with sulfuric acid and / or hydrochloric acid to separate the solid lignin.
[0025] 4. The preparation method according to item 3, wherein the acidification of the papermaking black liquor with carbonic acid comprises: using carbon dioxide to contact the papermaking black liquor with convection to reduce the pH of the papermaking black liquor to below 11, preferably to 8 to 10.5;
[0026] Preferably, the temperature for acidifying the papermaking black liquor with carbonic acid is 70 to 200°C, preferably 80 to 130°C.
[0027] 5. The preparation method according to item 3 or 4, wherein the liquid lignin is acidified with sulfuric acid and hydrochloric acid until the pH is ≤ 4.5, preferably until the pH is 1.5 to 4, and the solid lignin is separated;
[0028] Preferably, the temperature for acidifying the liquid lignin with sulfuric acid and hydrochloric acid is less than 200°C, more preferably 80-150°C, and further preferably 90-130°C.
[0029] 6. The preparation method according to any one of items 1 to 5, wherein the solid content of the papermaking black liquor is 8% to 70%, preferably 30% to 60%.
[0030] 7. A preparation method according to any one of items 1 to 6, wherein, in the separation step, the lignin separated from the papermaking black liquor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried to obtain dried lignin; preferably, the acid washing is carried out using any one or more of the following acids: sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, formic acid and acetic acid.
[0031] 8. The preparation method according to any one of items 1 to 7, wherein in the polymerization step, the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution and ammonia water;
[0032] Preferably, the pH of the alkaline solution is ≥ 10, more preferably pH ≥ 11;
[0033] Preferably, the cross-linking agent is selected from any one or more of oxalic acid, formic acid, acetic acid, phosphoric acid, methanol, ethanol, ethylene glycol, polyethylene glycol, formaldehyde, glutaraldehyde, phenol, resorcinol, hydroquinone, butyl rubber, N,N-methylenebisacrylamide, epichlorohydrin, ferric chloride, glucose, zinc gluconate, calcium gluconate, melamine, hexamethylenetetramine, ammonium phosphate, diammonium dihydrogen phosphate, diammonium hydrogen phosphate, melamine formaldehyde resin and phenolic resin;
[0034] Preferably, the cross-linking curing reaction temperature is 80 to 200°C, preferably 90 to 150°C;
[0035] Preferably, the cross-linking curing reaction time is 1 to 20 hours, preferably 8 to 16 hours;
[0036] Preferably, the dried lignin is crushed and then dissolved in an alkaline solution.
[0037] 9. The preparation method according to any one of items 1 to 8, wherein the pre-oxidation temperature is 100 to 250° C., preferably 160 to 210° C.; the pre-oxidation time is 1 to 24 hours, preferably 4 to 12 hours;
[0038] Preferably, the lignin polymer solid is crushed before pre-oxidation.
[0039] 10. The preparation method according to any one of items 1 to 9, wherein in the pre-carbonization step, the pre-carbonization temperature is 300 to 800° C., preferably 350 to 700° C.;
[0040] Preferably, the pre-carbonization time is 1 to 5 hours, preferably 1 to 3 hours;
[0041] Preferably, in the pre-carbonization step, the protective atmosphere is a non-oxidizing gas atmosphere.
[0042] 11. The preparation method according to any one of items 1 to 10, wherein in the gas phase deashing step, the gas phase deashing temperature is 400 to 1500°C, preferably 450 to 1400°C, more preferably 500 to 1300°C, further preferably 600 to 1200°C, and further preferably 650 to 1150°C;
[0043] Preferably, the gas phase deashing time is 3 to 400 min, preferably 10 to 300 min, more preferably 20 to 200 min;
[0044] Preferably, in the gas phase deashing step, the protective atmosphere is an inert gas atmosphere, preferably the inert gas is selected from any one or more of nitrogen, helium, argon and krypton, more preferably the inert gas is nitrogen or argon;
[0045] Preferably, the halogen element is selected from any one or more of fluorine, chlorine, bromine and iodine, more preferably chlorine;
[0046] Preferably, the halogen compound is selected from any one or more of the following: hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, a compound produced by thermal decomposition and selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide and bromine chloride, more preferably hydrogen chloride;
[0047] Preferably, in the gas phase deashing step, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element is 0.02 to 15:100, more preferably 0.06 to 7:100, and further preferably 0.1 to 6:100.
[0048] 12. The preparation method according to any one of items 1 to 11, wherein in the calcining step, the carbon material precursor 2 is crushed into particles with an average particle size D50 of 1 to 100 μm;
[0049] Preferably, the calcination temperature is 400 to 2000°C, more preferably 500 to 1800°C, further preferably 800 to 1600°C, further preferably 1000 to 1500°C, and most preferably 1100 to 1400°C;
[0050] Preferably, the calcination time is 0.01 to 20 h, more preferably 0.05 to 15 h, and further preferably 0.05 to 10 h;
[0051] Preferably, the protective atmosphere is a non-oxidizing gas atmosphere, and preferably the non-oxidizing gas is selected from any one, two or three of helium, nitrogen and argon.
[0052] 13. The preparation method according to any one of items 1 to 12, wherein the carbon material precursor is crushed, calcined under a protective atmosphere, and further comprises a coating step: coating with pyrolytic carbon;
[0053] Preferably, the coating is performed using a chemical vapor deposition method.
[0054] 14. The preparation method according to any one of items 1 to 13, wherein the thermal weight loss rate of the lignin-based resin at 450° C. is less than 42%, preferably less than 40%;
[0055] The thermal weight loss rate at 1300° C. is below 72%, preferably below 70%.
[0056] 15. The preparation method according to any one of items 1 to 14, wherein the lignin-based resin is cracked at 300°C to obtain a gas phase product, and in the chromatogram obtained by gas chromatography-mass spectrometry analysis, the vinylguaiacol peak area accounts for less than or equal to 1%, preferably less than or equal to 0.5%;
[0057] The vanillone peak area accounts for less than or equal to 2%, preferably less than or equal to 1.5%;
[0058] The acetosyringone peak area accounts for less than or equal to 1%, preferably less than or equal to 0.7%.
[0059] 16. A carbon material for a battery produced by the method for producing a carbon material for a battery according to any one of items 1 to 15.
[0060] 17. A lignin-based resin, wherein its thermal weight loss rate at 450°C is below 42%, preferably below 40%;
[0061] The thermal weight loss rate at 1300° C. is below 72%, preferably below 70%.
[0062] 18. The lignin-based resin according to item 17, wherein in the chromatogram obtained by gas phase product obtained by pyrolysis at 300°C and gas chromatography-mass spectrometry analysis, the peak area of vinylguaiacol accounts for less than or equal to 4%, preferably less than or equal to 1%;
[0063] The vanillone peak area accounts for less than or equal to 4%, preferably less than or equal to 2%;
[0064] The acetosyringone peak area accounts for less than or equal to 3%, preferably less than or equal to 1%.
[0065] 19. Use of a carbon material for a battery prepared by the method for preparing a carbon material for a battery according to any one of items 1 to 15 or a carbon material for a battery prepared based on the lignin-based resin according to item 17 or 18 in a hard carbon material for a battery;
[0066] Preferably, the battery hard carbon material is a sodium ion battery hard carbon material or a battery hard carbon negative electrode material.
[0067] Effects of the Invention
[0068] (1) The present application uses papermaking black liquor as raw material. By separating the lignin in the papermaking black liquor and then subjecting it to cross-linking, curing, pre-oxidation and other treatments, the lignin is polymerized into a lignin-based resin with a higher molecular weight, thereby improving the phenomenon of expansion and foaming during lignin carbonization. Foaming will affect production, including the amount of material loaded in the sagger, the removal of the material after dry distillation, and the crushing process, which all need to be adjusted, which will increase costs and make industrialization more difficult.
[0069] (2) The present application uses a high molecular weight lignin-based resin as a hard carbon precursor, which has the advantages of a wide range of sources and low cost of biomass precursors (apricot shells, coconut shell carbon, bamboo chips, walnut shells, etc.) and the advantages of adjustable structure and higher performance of phenolic resin precursors. It is an excellent hard carbon precursor material;
[0070] (3) The method of the present application is simple to operate, has low pre-carbonization temperature, low energy consumption, low production cost, and significant economic benefits;
[0071] (4) The dried high-purity lignin obtained by the separation step of the present application has low ash content, high fixed carbon content, and low sulfur content, which is more conducive to the subsequent preparation of carbon materials for batteries;
[0072] (5) This application expands the application scope of papermaking black liquor, turning waste into treasure and increasing its added value;
[0073] (6) The carbon material for batteries prepared by the method of the present application has low ash content, controllable specific surface area, uniform particle size, and high bulk density; it has excellent sodium insertion and removal capabilities, with an initial coulombic efficiency of more than 88%, a gram capacity of more than 300 mAh / g, and good electrochemical properties; it has good cycle stability, and after 1,000 cycles, the capacity retention rate is more than 86%, and the coulombic efficiency is close to 100%; it can meet various performance requirements of sodium ion battery negative electrode materials and has broad application prospects; it has good high-current charging performance and has good application prospects in electric vehicles and energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Figure 1 This is a process flow chart of a specific implementation method of the present application.
[0075] Figure 2 This is a TGA curve diagram of the lignin-based resin of Example 1 of the present application and the lignin of Comparative Example 1.
[0076] Figure 3A This is the gas chromatography-mass spectrometry chromatogram of the lignin of Comparative Example 1.
[0077] Figure 3B This is a gas chromatography-mass spectrometry chromatogram of the lignin-based resin of Example 1 of the present application.
[0078] Figure 4This is the DSC graph of lignin in Comparative Example 1.
[0079] Figure 5 This is the DSC graph of the lignin-based resin of Example 1 of the present application.
[0080] Figure 6 This is the SEM image (2k×) of the lignin of Comparative Example 1.
[0081] Figure 7 This is the SEM image (10k×) of the lignin of Comparative Example 1.
[0082] Figure 8 This is the SEM image (2k×) of the lignin-based resin of Example 1 of the present application.
[0083] Fig. 9 This is the SEM image (10k×) of the lignin-based resin of Example 1 of the present application. DETAILED DESCRIPTION
[0084] The specific embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0085] It should be noted that the words "including" or "comprising" mentioned throughout the specification and claims are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0086] On the one hand, the present application provides a method for preparing a carbon material for a battery, such as Figure 1 As shown, it includes the following steps:
[0087] Separation: separating lignin from papermaking black liquor and drying the lignin;
[0088] Polymerization: Dissolve the dried lignin in an alkaline solution, then add a cross-linking agent to perform a cross-linking curing reaction to obtain a lignin polymer solid;
[0089] Pre-oxidation: pre-oxidizing the lignin polymer solid to obtain a lignin-based resin;
[0090] Pre-carbonization: pre-carbonizing the lignin-based resin under a protective atmosphere to obtain a carbon material precursor 1;
[0091] Gas phase deashing: in a protective atmosphere and under the action of a halogen compound and / or a halogen element, the carbon material precursor 1 is gas phase deashed to obtain a carbon material precursor 2;
[0092] Calcination: The carbon material precursor is crushed and calcined under a protective atmosphere to obtain a carbon material for a battery.
[0093] The "papermaking black liquor" of this application refers to the wastewater generated by the alkali (caustic soda) pulping process of the papermaking industry, which contains a large amount of lignin, hemicellulose, pigments, pentose, nitrogen, phosphorus, potassium and other dissolutions. Since the wastewater is dark brown, it is called papermaking black liquor. The straw and other raw materials used for papermaking contain substances such as cellulose, lignin and hemicellulose. Only cellulose (about 40%) is used for papermaking, while about 25% of lignin and about 28% of hemicellulose, as well as pigments, pentose, nitrogen, phosphorus, potassium, etc. are discarded with the papermaking black liquor. Because the papermaking black liquor contains a large amount of suspended solids, organic pollutants and toxic substances, direct discharge into the water will cause serious pollution. Its main hazards are: papermaking wastewater containing a large amount of fiber, pigment and inorganic salt will make the water black and have a special stench; the biochemical oxygen demand (BOD) of papermaking black liquor containing high concentration of organic pollutants can be as high as 5000-40000g / L, which will consume a large amount of dissolved oxygen in the water and affect the water quality; the large amount of alkaline substances in papermaking black liquor will cause the pH value of the water to rise sharply and destroy the balance of the water environment.
[0094] If the papermaking black liquor cannot be effectively treated and is directly discharged, it will not only seriously pollute the environment but also cause a large amount of waste of resources. The present application expands the application scope of papermaking black liquor, turns waste into treasure, and increases the added value of papermaking black liquor.
[0095] In some embodiments, the solid content of the papermaking black liquor is 8% to 70%, for example, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, %, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, etc., preferably 30% to 60%. The present application uses a moisture meter to measure the solid content of the papermaking black liquor.
[0096] In some embodiments, in the separation step, the papermaking black liquor is acidified with an acidifier to separate lignin from the papermaking black liquor; wherein the acidifier is selected from any one or more of carbonic acid, sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid, and preferably the acidifier is selected from one or two or three of carbonic acid, sulfuric acid and hydrochloric acid. By adjusting the type and amount of the acid, the particle size range and ash content of the precipitated lignin can be controlled.
[0097] In some embodiments, in the separation step, hydrochloric acid is used to acidify the papermaking black liquor to reduce the pH of the papermaking black liquor to pH ≤ 4.5, for example, it can be 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, etc., preferably reduced to a pH of 1.5-4, to separate the lignin.
[0098] In some preferred embodiments, in the separation step, carbonic acid is used to acidify the papermaking black liquor to separate liquid lignin, and then sulfuric acid and / or hydrochloric acid are used to acidify the liquid lignin to separate solid lignin. Acidification with carbonic acid first can precipitate the high molecular weight lignin in the papermaking black liquor, which, on the one hand, makes the molecular weight of the lignin large and more concentrated; on the other hand, less sulfuric acid and hydrochloric acid are consumed, reducing costs and reducing wastewater for precipitating lignin.
[0099] In some embodiments, in the separation step, carbon dioxide is used for convective contact with papermaking black liquor to reduce the pH of the papermaking black liquor to below 11, for example, it can be 11, 10.5, 10, 9.5, 9, 8.5, 8, 7.5, 7, 6.5, 6, 5.5, 5, 4.5, etc., preferably to 8-10.5, to separate liquid lignin, and then use sulfuric acid and hydrochloric acid to acidify the liquid lignin until the pH is ≤4.5, for example, it can be 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, etc., preferably until the pH is 1.5-4, to separate solid lignin.
[0100] In the above embodiment, the temperature for acidifying the papermaking black liquor with carbonic acid is 70-200°C, for example, it can be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, etc., preferably 80-130°C.
[0101] In the above embodiment, the temperature for acidifying the liquid lignin with sulfuric acid and hydrochloric acid is less than 200°C, for example, it can be 199°C, 195°C, 190°C, 185°C, 180°C, 175°C, 170°C, 165°C, 160°C, 155°C, 150°C, 145°C, 140°C, 135°C, 130°C, 125°C, 120°C, 115°C, 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, etc., more preferably 80-150°C, and further preferably 90-130°C.
[0102] In some embodiments, in the separation step, the lignin separated from the papermaking black liquor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried to obtain dried lignin; preferably, the acid washing is carried out using any one or more of the following acids: sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, formic acid and acetic acid.
[0103] In some embodiments, in the polymerization step, the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution and ammonia water; the pH of the alkaline solution is ≥ 10, for example, it can be 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14, etc., preferably pH ≥ 11. In the present application, the sodium hydroxide solution can be an aqueous sodium hydroxide solution, the potassium hydroxide solution can be an aqueous potassium hydroxide solution, and the calcium hydroxide solution can be an aqueous calcium hydroxide solution.
[0104] In some embodiments, in the polymerization step, the cross-linking agent can be selected from any one or more of oxalic acid, formic acid, acetic acid, phosphoric acid, methanol, ethanol, ethylene glycol, polyethylene glycol, formaldehyde, glutaraldehyde, phenol, resorcinol, hydroquinone, butyl rubber, N, N-methylenebisacrylamide, epichlorohydrin, ferric chloride, glucose, zinc gluconate, calcium gluconate, melamine, hexamethylenetetramine, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, melamine formaldehyde resin and phenolic resin. In some embodiments, the cross-linking agent includes polyethylene glycol, formaldehyde and hexamethylenetetramine. In some embodiments, the cross-linking agent is polyethylene glycol, formaldehyde and hexamethylenetetramine. In some embodiments, the cross-linking agent is melamine, formaldehyde and hexamethylenetetramine.
[0105] In some embodiments, the cross-linking curing reaction temperature is 80-200°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., preferably 90-150°C, and the cross-linking curing reaction time is 1-20h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc., preferably 8-16h. The appropriate temperature curve allows the active sites on the liquid lignin to fully contact with the cross-linking agent, and at the same time, the volatilization rate of the volatile substances in the solvent is adjusted by controlling the polymerization temperature, so that a suitable pore structure is generated inside the lignin during cross-linking polymerization.
[0106] In some embodiments, the cross-linking curing reaction is a temperature rising process. In some embodiments, the cross-linking curing reaction is: first react at 90-100°C for 6-14h, then react at 100-125°C for 1-3h, and finally react at 125-150°C for 1-3h. In some embodiments, the cross-linking curing reaction is: first react at 90-98°C for 6-14h, then react at 100-125°C for 1-3h, and finally react at 128-150°C for 1-3h. In some embodiments, the cross-linking curing reaction is: first react at 90°C for 6-14h, then react at 105°C for 1-3h, and finally react at 150°C for 1-3h. In some embodiments, the cross-linking curing reaction is: first react at 90°C for 12h, then react at 105°C for 2h, and finally react at 105°C for 2h. In some embodiments, the cross-linking curing reaction is: first react at 90-100°C for 7-15h, and then react at 100-110°C for 1-3h. In some embodiments, the cross-linking curing reaction is: react at 80-88°C for 1-20h. In some embodiments, the cross-linking curing reaction is: react at 155-200°C for 1-20h. In some embodiments, the cross-linking curing reaction is: first react at 80-88°C for 0.5-16h, and then react at 90-150°C for 0.5-4h. In some embodiments, the cross-linking curing reaction is: first react at 90-150°C for 0.5-10h, and then react at 155-200°C for 0.5-10h. In some embodiments, the cross-linking curing reaction is: first react at 90-150°C for 4-8h, and then react at 155-200°C for 4-8h. In some embodiments, the cross-linking curing reaction is: first react at 80-90° C. for 0.5-16 h, then react at 90-160° C. for 0.25-2 h, and finally react at 160-200° C. for 0.25-2 h.
[0107] The pre-oxidation step of the present application can strengthen the cross-linking degree of the polymer. In some embodiments, the pre-oxidation temperature is 100-250°C, for example, it can be 100°C, 120°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc., preferably 160-210°C, and the pre-oxidation time is 1-24h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, etc., preferably 4-12h. Appropriate pre-oxidation temperature and time can incorporate oxygen atoms into the network structure of the cross-linked and cured lignin polymer, thereby improving the performance of the product after carbonization. At the same time, appropriate pre-oxidation conditions can also remove some volatile substances and adjust the internal pore structure of the lignin-based resin.
[0108] In some embodiments, the lignin polymer solid is crushed and then pre-oxidized. In some embodiments, the average particle size D50 of the lignin polymer solid particles obtained after the lignin polymer solid is crushed is 20 to 50 μm, for example, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, etc. The "average particle size D50" in this application refers to the particle size corresponding to the cumulative particle size distribution percentage of a sample reaching 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called the median diameter or median particle size.
[0109] The average particle size D50 of the present application is measured by Malvern laser particle size analyzer Mastersizer 3000E.
[0110] In some embodiments, the pre-carbonization temperature is 300-800° C., for example, 300° C., 320° C., 340° C., 350° C., 360° C., 380° C., 400° C., 420° C., 440° C., 450° C., 460° C., 480° C., 500° C., 520° C., 540° C., 550° C., 560° C., 580° C., 600° C., 620° C., 640° C., 650° C., 660° C., 680° C., 700° C., 720° C., 740° C., 750° C., 760° C., 780° C., 800° C., etc., preferably 350-700° C. If the pre-carbonization temperature is too low, the volatile matter content in the carbon material precursor is high, which will cause the volatile matter to pollute and damage the equipment during subsequent carbonization; if the pre-carbonization temperature is too high, it will increase the cost and affect the product performance. After low-temperature pre-carbonization, the present application can further reduce the volatile components by using gas deashing, so that a hard carbon product with excellent performance can be prepared at a lower pre-carbonization temperature.
[0111] The pulverizer used for pulverization in the present application is not particularly limited, and for example, a jet mill, a rod mill, a vibration ball mill, a hammer mill or a steel mill can be used.
[0112] The pre-carbonization of the lignin particles is carried out in a protective atmosphere, and the protective atmosphere may be a non-oxidizing gas, such as helium, nitrogen or argon. In addition, the pre-carbonization may also be carried out under reduced pressure, for example, below 10 kPa. The time of the pre-carbonization is not particularly limited, and may be, for example, 1 to 5 hours, such as 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.2, 2.4, 2.5, 2.6, 2.8, 3, 3.2, 3.4, 3.5, 3.6, 3.8, 4, 4.2, 4.4, 4.5, 4.6, 4.8, 5, etc., preferably 1 to 3 hours.
[0113] In some embodiments, the pre-carbonization temperature is 300-800° C., and the pre-carbonization time is 1-5 hours.
[0114] In some embodiments, the pre-carbonization temperature is 350-700° C., and the pre-carbonization time is 1-3 hours.
[0115] Carbon derived from papermaking black liquor is plant-derived carbon and has voids derived from ducts and sieve tubes. Therefore, it can be formed into an optimal pore structure through pre-carbonization and is suitable for use as an electrode material having excellent discharge capacity and showing excellent first coulombic efficiency.
[0116] Papermaking black liquor contains a lot of metal elements. When the carbonaceous material made from it is used as a battery electrode, it will have an adverse effect on the electrochemical characteristics and safety of the battery. Therefore, it is necessary to reduce the metal elements in the carbonaceous material as much as possible. After the pre-carbonization step, the residual metal elements can be removed by the gas phase deashing step.
[0117] The halogen compound and / or halogen element used for gas phase deashing is not particularly limited. For example, the halogen element can include: fluorine, chlorine, bromine, iodine element, and the preferred halogen element is chlorine. The halogen compound can include: hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and a compound selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide and bromine chloride by thermal decomposition, and the preferred halogen compound is hydrogen chloride. In some embodiments, gas phase deashing is carried out under a protective atmosphere and under the action of hydrogen chloride. In some embodiments, gas phase deashing is carried out under a protective atmosphere and under the action of chlorine.
[0118] Furthermore, the halogen compound and / or the halogen element can be mixed with a protective atmosphere for use. The protective atmosphere is not particularly limited as long as it is a gas that does not participate in the reaction at the gas phase deashing temperature. For example, it can be an inert gas, and further examples include nitrogen, helium, argon, krypton or a mixture of these gases, preferably nitrogen or argon.
[0119] In gas phase deashing, as long as sufficient deashing can be achieved, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element is not particularly limited. In some embodiments, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element may be 0.02 to 15:100, for example, 0.02:100, 0.06:100, 0.1:100, 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, etc., preferably 0.06 to 7:100, and more preferably 0.1 to 6:100.
[0120] In some embodiments, the gas phase deashing temperature is 400-1500°C, for example, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 90 The deashing temperature is preferably 0° C., 950° C., 1000° C., 1050° C., 1100° C., 1150° C., 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., 1450° C., 1500° C., etc., preferably 450 to 1400° C., more preferably 500 to 1300° C., further preferably 600 to 1200° C., and further preferably 650 to 1150° C. If the temperature is less than 400° C., the deashing efficiency is reduced and the deashing is insufficient, and if the temperature is more than 1500° C., activation by the halogen compound and / or the halogen element occurs.
[0121] In addition, the gas phase deashing time is not particularly limited, but is preferably 3 to 400 minutes, for example, 3°C, 5°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., more preferably 10 to 300 minutes, and further preferably 20 to 200 minutes. As for the gas phase deashing temperature and time, the higher the temperature, the more the deashing is advanced, and the longer the time, the more the deashing is advanced.
[0122] The device used for gas phase deashing is not particularly limited, as long as it can heat the carbon material precursor while mixing it with the protective atmosphere and the mixed gas of the halogen compound and / or the halogen element, for example, a fluidized bed reactor can be used in a continuous or intermittent layer flow method such as a fluidized bed. The supply amount (flow rate) of the mixed gas is also not particularly limited.
[0123] In the calcination step, the carbon material precursor 2 obtained in the gas phase deashing step needs to be crushed first, and then calcined under a protective atmosphere. Specifically, the carbon material precursor 2 is crushed into an average particle size D50 of 1 to 100 μm, for example, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc. Although crushing can also be performed after calcination, the carbon material precursor will become hard after calcination, making it difficult to control the particle size distribution after crushing. Therefore, crushing is required after the gas phase deashing step and before calcination under a protective atmosphere. Controlling the average particle size D50 of the carbon material precursor 2 within the above range can further improve the processing performance of the battery carbon material used as the battery negative electrode active component and improve the first coulomb efficiency of the battery carbon material. The pulverizer used for pulverization is not particularly limited, and for example, a jet mill, a rod mill, a vibration ball mill, a hammer mill or a steel mill can be used, and a jet mill equipped with a classifier is preferred.
[0124] In some embodiments, the calcination temperature is 400-2000°C, for example, it may be 400°C, 410°C, 420°C, 450°C, 460°C, 480°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, etc., more preferably 500-1800°C, further preferably 800-1600°C, further preferably 1000-1500°C, and most preferably 1100-1400°C. If the calcination temperature is too low, the carbonization will be incomplete and the irreversible capacity will increase; if the calcination temperature is too high, the discharge capacity of the battery will decrease.
[0125] The calcination of the present application is carried out in a protective atmosphere. As a protective atmosphere, it can be a non-oxidizing gas, specifically helium, nitrogen or argon, etc., which can be used alone or in combination. In addition, calcination can be carried out under reduced pressure, for example, calcination can be carried out below 10kPa. The calcination time is also not particularly limited, for example, 0.01 to 20 hours can be carried out, for example, 0.01h, 0.1h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc., preferably 0.05 to 15h, more preferably 0.05 to 10h.
[0126] In some embodiments, the methods of the present application, such as Figure 1 As shown, the carbon material precursor is crushed, calcined under a protective atmosphere, and a coating step may be included. The coating step is a step of coating the burnt product obtained after calcination with pyrolytic carbon. The coating with pyrolytic carbon can be carried out using a chemical vapor deposition method (CVD method). For example, the burnt product is contacted with a gaseous straight-chain hydrocarbon or a cyclic hydrocarbon, and the gaseous straight-chain hydrocarbon or the cyclic hydrocarbon diffuses on the surface and inside of the burnt product, and pyrolyzes at a certain temperature, and the carbon refined by pyrolysis is vapor-deposited on the surface and inside of the burnt product. Chemical vapor deposition is a well-known method. The coating step can control the specific surface area of the resulting carbon material for batteries.
[0127] The pyrolytic carbon used in the present application is not particularly limited, as long as it is a substance that can reduce the specific surface area of the carbonaceous material.
[0128] In some embodiments, the number of carbon atoms in the carbon source of pyrolytic carbon is not limited, and can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, etc. The number of carbon atoms is preferably 1-25, more preferably 1-20, further preferably 1-15, and most preferably 1-10.
[0129] In some embodiments, the carbon source of pyrolytic carbon is not particularly limited, and examples thereof include: methane, ethane, propane, butane, pentane, hexane, octane, nonane, decane, ethylene, propylene, butene, pentene, hexene, acetylene, cyclopentane, cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclopropene, cyclopentene, cyclohexene, cycloheptene, cyclooctene, decahydronaphthalene, norbornene, methylcyclohexane, norbornadiene, benzene, toluene, xylene, mesitylene, isopropylbenzene, butylbenzene, ethylene, and polystyrene.
[0130] The coating device is not limited, and the coating can be carried out by a continuous or intermittent layer flow method using a fluidized bed reactor or the like. The supply amount (flow rate) of the gas is not limited.
[0131] In some embodiments, after the pre-carbonization step and before the gas phase deashing step, a washing and drying step is further included: the carbon material precursor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried; preferably, the acid washing is performed using any one or more of the following acids: sulfuric acid, hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, formic acid and acetic acid. Adding the washing and drying step can further remove impurities such as silicon and calcium that are not effectively removed by gas phase deashing.
[0132] Thermogravimetric analysis
[0133] In this application, thermogravimetric analysis (TGA) refers to a thermal analysis technique that measures the relationship between the mass and temperature change of a sample to be tested under a program-controlled temperature, which is used to study the thermal stability and composition of the material. TGA is a commonly used detection method in research and development and quality control. In actual material analysis, thermogravimetric analysis is often used in conjunction with other analysis methods to perform comprehensive thermal analysis and comprehensively and accurately analyze materials. The curve recorded by a thermogravimetric analyzer is called a TGA curve.
[0134] In some embodiments, the thermal weight loss rate of the lignin-based resin when heated from room temperature to 450° C. is less than 42%, preferably less than 40%, for example, less than 42%, less than 41.5%, less than 41%, less than 40.5%, less than 40%, less than 39.5%, less than 39%, less than 38.5%, less than 38%, less than 37.5%, less than 37%, less than 36.5%, less than 36%, less than 35.5%, less than 35%, less than 34.5%, less than 34%, less than 33.5%, less than 33%, less than 32.5%, less than 32%, less than 31.5%, less than 31%. The thermal weight loss rate of the lignin-based resin when the temperature is increased from room temperature to 1300°C is below 72%, preferably below 70%, for example, below 72%, below 71.5%, below 71%, below 70.5%, below 70%, below 69.5%, below 69%, below 68.5%, below 68%, below 67.5%, below 67%, below 66.5%, below 66%, below 65.5%, below 65%, below 64.5%, below 64%, below 63.5%, below 63%, below 62.5%, below 62%, below 61.5%, below 61%, etc.
[0135] In some embodiments, the thermal weight loss rate is obtained by performing weight loss analysis on the lignin-based resin using a thermogravimetric analyzer (TA TGA thermogravimetric analyzer Q50), wherein the thermogravimetric analyzer is set at a temperature range of 30° C. to 1330° C. and a heating rate of 1° C. / min.
[0136] In some embodiments, the TGA curve of the lignin-based resin is as follows: Figure 3B As shown, its thermal weight loss rate at 450°C is 39.39%, and its thermal weight loss rate at 1300°C is 68.61%.
[0137] Gas chromatography-mass spectrometry
[0138] Gas chromatography-mass spectrometry (GC-MS) consists of a gas chromatograph combined with a mass spectrometer, and is suitable for analyzing small molecules, volatile, thermally stable, and vaporizable compounds. It can be applied to pharmaceutical product testing, environmental analysis (water, air, soil), agricultural regulation, food safety, beverages and aquatic products, perfume and daily chemical analysis, and unknown sample identification. GC-MS testing has the following advantages: a wide range of applications, and can analyze volatile components and low molecular weight compounds (relative molecular weight <1000), and is widely applicable to various organic or inorganic compounds with a boiling point below 400°C; high sensitivity, and can detect the amount of substances at the ng / g (10-9) level; fast analysis speed, generally a sample can be analyzed within a few minutes or tens of minutes; high separation efficiency, and can analyze organic homologues, complex compounds, isomers, and chiral isomers, etc.
[0139] In some embodiments, the lignin-based resin is cracked at 300° C. to obtain a gas phase product, and the gas phase product is analyzed by gas chromatography-mass spectrometry. In the gas chromatography-mass spectrometry chromatogram, the peak area of vinylguaiacol accounts for ≤4%, the peak area of tantalum ketone accounts for ≤4%, and the peak area of acetosyringone accounts for ≤3%; for example, the peak area of vinylguaiacol may account for ≤4%, ≤3.5%, ≤3%, ≤2.5%, ≤2%, ≤1.5%, ≤1%, ≤0.9%, ≤0.8%, ≤0.7%, ≤0.6%, ≤0.5%, ≤0.4%, ≤0.3%, ≤0.2%, ≤0.1%, etc., and the peak area of tantalum ketone accounts for ≤4%. The peak area ratio of acetosyringone can be ≤4%, ≤3.5%, ≤3%, ≤2.5%, ≤2%, ≤1.9%, ≤1.8%, ≤1.7%, ≤1.6%, ≤1.5%, ≤1.4%, ≤1.3%, ≤1.2%, ≤1.1%, ≤1%, ≤0.9%, ≤0.8%, ≤0.7%, ≤0.6%, ≤0.5%, ≤0.4%, etc., and the peak area ratio of acetosyringone can be ≤3%, ≤2.5%, ≤2%, ≤1.5%, ≤1%, ≤0.9%, ≤0.8%, ≤0.7%, ≤0.6%, ≤0.5%, ≤0.4%, ≤0.3%, ≤0.2%, ≤0.1%, etc.
[0140] The mass spectrometry chromatography used in the mass spectrometry chromatography analysis of the present application is Agilent 5977B GC / MSD.
[0141] In some embodiments, the lignin-based resin is cracked at 300° C. to obtain a gas product, which is analyzed by gas chromatography-mass spectrometry. In the gas chromatography-mass spectrometry chromatogram, the peak area of vinylguaiacol accounts for ≤1%, the peak area of butylene glycol accounts for ≤2%, and the peak area of acetosyringone accounts for ≤1%.
[0142] Specifically, the peak area percentage described in the present application refers to the area percentage after removing the influence of the solvent.
[0143] In some embodiments, the GC-MS chromatogram of the lignin-based resin is as follows: Figure 3B shown.
[0144] Differential Scanning Calorimetry
[0145] Differential scanning calorimetry (DSC) is a technique that measures the heat flow rate of a sample relative to a reference material as it changes with temperature or time under temperature program control. The curve recorded by the differential scanning calorimeter is called the DSC curve, which is generally measured in W / g or mW / mg (i.e., the power flowing to each gram of sample) as the ordinate and in temperature T or time t as the abscissa. It can measure a variety of thermodynamic and kinetic parameters, such as specific heat capacity, reaction heat, transition heat, phase diagram, reaction rate, crystallization rate, polymer crystallinity, sample purity, etc. This method has a wide temperature range (-175 to 725°C), high resolution, and small sample size. It is suitable for the analysis of inorganic substances, organic compounds, and drugs.
[0146] In some embodiments, the lignin-based resin is subjected to DSC detection using a differential scanning calorimeter (TA DSC differential scanning calorimeter Q2000), and the temperature is increased from room temperature to 250° C. at 3° C. / min to analyze the heat release change of the lignin-based resin during the heating process.
[0147] In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin comprises an exothermic peak at about 202°C ± 10°C. In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin comprises an exothermic peak at about 202°C ± 5°C. In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin comprises an exothermic peak at about 202°C ± 2°C.
[0148] In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin comprises an exothermic peak at about 202°C±10°C, and the onset of the exothermic peak is 168.5°C±5°C.
[0149] In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin comprises an exothermic peak near 202°C±10°C, the onset of the exothermic peak is 168.5°C±5°C, and the peak area of the exothermic peak is 234 J / g±2 J / g.
[0150] In some embodiments, the differential scanning calorimetry thermogram of the lignin-based resin is as follows: Figure 5 shown.
[0151] On the other hand, the present application also provides a carbon material for a battery prepared by any of the aforementioned methods for preparing a carbon material for a battery.
[0152] In yet another aspect, the present application also provides a lignin-based resin, which is as described in any lignin-based resin in the aforementioned method.
[0153] On the other hand, the present application also provides an application of a battery carbon material prepared by any of the aforementioned methods for preparing a battery carbon material or a battery carbon material prepared based on any of the aforementioned lignin-based resins in battery hard carbon materials.
[0154] In some embodiments, the battery hard carbon material is a sodium ion battery hard carbon material or a battery hard carbon negative electrode material.
[0155] Example
[0156] The present application provides a general and / or specific description of the materials and experimental methods used in the experiments. In the following examples, the reagents or instruments used without indicating the manufacturer are all conventional reagents or instruments that can be obtained commercially.
[0157] Example 1
[0158] Take papermaking black liquor with a solid content of 60% (taken from Shandong Huatai Group), stir it at 90°C, add hydrochloric acid solution to adjust pH≤4 during stirring, so that lignin precipitates, and after centrifugal filtration, dry the filter residue at 110°C, crush it with a steel mill to obtain lignin particles, dissolve the lignin particles in a sodium hydroxide solution with a pH of 12, add polyethylene glycol and formaldehyde, and add hexamethylenetetramine at the same time, heat the mixed liquid to 90°C, keep it for 12h, heat it to 105°C and keep it for 2h, and then heat it to 150°C and keep it for 2h to obtain lignin polymer solid ; After the lignin polymer solid is crushed, it is pre-oxidized at 200°C for 12 hours to obtain a lignin-based resin, and the lignin-based resin is pre-carbonized at 450°C in a nitrogen atmosphere to obtain a carbon material precursor 1; the carbon material precursor 1 is gas-phase deashed at 900°C, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 is introduced to obtain a carbon material precursor 2; the carbon material precursor 2 is crushed into particles with a D50 of 8μm by a gas flow mill, and then high-temperature calcined at 1200°C for 2 hours in a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 40%.
[0159] Example 2
[0160] The difference between this embodiment and embodiment 1 is that the carbon material precursor 2 is crushed into particles with a D50 of 8 μm and then calcined at 1200°C for 2 hours in a nitrogen atmosphere, and then mixed with 1 / 10 the mass of the obtained sample and heat treated at 750°C for 1 hour in a closed container to obtain a battery hard carbon material with a total yield of 38%.
[0161] Example 3
[0162] The difference between this embodiment and embodiment 1 is that after adding polyethylene glycol and formaldehyde and adding hexamethylenetetramine at the same time, the mixed liquid is heated to 90° C. and maintained for 16 hours to obtain a lignin polymer solid.
[0163] Example 4
[0164] The difference between this embodiment and embodiment 1 is that after adding polyethylene glycol and formaldehyde and adding hexamethylenetetramine at the same time, the mixed liquid is heated to 90° C., maintained for 12 hours, and then heated to 105° C. and maintained for 4 hours to obtain a lignin polymer solid.
[0165] Example 5
[0166] The difference between this embodiment and embodiment 1 is that the pre-oxidation temperature is 160°C.
[0167] Example 6
[0168] The difference between this embodiment and embodiment 1 is that the pre-oxidation temperature is 100°C.
[0169] Example 7
[0170] The difference between this embodiment and embodiment 1 is that the pre-oxidation temperature is 250°C.
[0171] Example 8
[0172] The difference between this embodiment and embodiment 1 is that the pre-oxidation time is 4 hours.
[0173] Example 9
[0174] The difference between this embodiment and embodiment 1 is that the pre-oxidation time is 1 hour.
[0175] Example 10
[0176] The difference between this embodiment and embodiment 1 is that the pre-oxidation time is 24 hours.
[0177] Comparative Example 1
[0178] Take papermaking black liquor with a solid content of 60% (taken from Shandong Huatai Group), stir it at 90°C, add hydrochloric acid solution during the stirring process to adjust the pH value to ≤4, so that lignin precipitates, and after centrifugal filtration, dry the filter residue at 110°C, and use a steel mill to grind it to obtain lignin particles; pre-carbonize the lignin particles at 450°C under a nitrogen atmosphere. During the carbonization process, the lignin expands and foams severely, and the volume expansion rate is ≥200%, thereby obtaining a carbon material precursor 1; use a gas flow mill to grind the carbon material precursor 1 into particles with a D50 of 8μm, and then calcine them at 1200°C for 2h under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 21%.
[0179] Comparative Example 2
[0180] Take papermaking black liquor with a solid content of 60% (obtained from Shandong Huatai Group), stir it at 90°C, add hydrochloric acid solution to adjust the pH to 4 during the stirring process, so that lignin precipitates, and after centrifugal filtration, dry the filter residue at 110°C, and grind it with a steel mill to obtain lignin particles. Dissolve the lignin particles in a sodium hydroxide solution with a pH of 12, add polyethylene glycol and formaldehyde, and heat the mixed liquid to 90°C, keep it for 12h, then heat it to 105°C and keep it for 2h, and then heat it to 150°C and keep it for 2h to obtain to a lignin polymer solid; after the lignin polymer solid is crushed, it is pre-carbonized at 450°C in a nitrogen atmosphere to obtain a carbon material precursor one; the carbon material precursor one is gas-phase deashed at 900°C, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 is introduced to obtain a carbon material precursor two; the carbon material precursor two is crushed into particles with a D50 of 8μm by a jet mill, and then high-temperature calcined at 1200°C for 2h in a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 34%.
[0181] Comparative Example 3
[0182] Take apricot shell fragments, pre-carbonize them at 450°C under a nitrogen atmosphere, and then crush them to obtain an apricot shell carbon precursor one. Soak the carbon material precursor one in a hydrochloric acid solution and then filter it. After repeating three times, wash it with deionized water until the pH of the filtrate is ≥6. After drying, gas phase deashing is carried out at 900°C, during which a mixed gas of chlorine and nitrogen with a volume ratio of 1:100 is introduced to obtain an apricot shell carbon precursor two; the carbon material precursor two is crushed into particles with a D50 of 8μm by a gas flow mill, and then high-temperature roasted at 1200°C for 2h under a nitrogen atmosphere to obtain a battery hard carbon material with a total yield of 19%.
[0183] The electrochemical properties of the battery hard carbon materials of each embodiment and comparative example were tested according to the following method:
[0184] A slurry of 96 parts of hard carbon material, 1.5 parts of CMC, 1.5 parts of SBR and 1 part of SP mixed with water was evenly coated on the copper foil, baked in an oven at 90°C for 30-40 minutes and cut into 12 mm diameter discs to obtain an active material loading of 3-3.5 mg / cm 2 The electrode sheet was then prepared in a glove box with a protective gas atmosphere. The electrolyte was 1.5M NaPF6 (the volume ratio of EC:DEC:EMC was 1:2:2), the separator was glass fiber (GF / A), and the positive electrode was a sodium sheet.
[0185] For the half-cell prepared as above, the charge and discharge of the half-cell was tested using a battery testing device (manufactured by Wuhan Blue Electric). The process of embedding sodium ions into the hard carbon negative electrode is called "discharge", and the process of de-embedding sodium ions from the hard carbon negative electrode is called "charge". During the test, the half-cell was first allowed to stand for 8 hours, and then discharged to 0V using a constant current of 0.1C (about 30mA / g). When the voltage reached 0V, constant voltage discharge was performed at 0V until the current value reached 0.01mA. The value obtained by dividing the amount of electricity supplied by the load of the hard carbon material on the electrode was the discharge capacity of the hard carbon (mAh / g). After the discharge was completed, the battery was allowed to stand for 10 minutes, and then sodium ions were de-embedded from the negative electrode. The battery was charged to 2V at a constant current of 0.1C (about 30mA / g). The value obtained by dividing the amount of electricity supplied by the load of the hard carbon material on the electrode was the charge capacity of the hard carbon (mAh / g). The capacity at this time was defined as the gram capacity of the hard carbon material (mAh / g), and the percentage of the charge capacity to the discharge capacity was called the first coulomb efficiency (%). For the experimental batteries made from the same batch of samples, 6 groups of half-cells were tested under the same environmental conditions. The 6 gram capacities and first coulombic efficiencies were obtained. After removing the lowest and highest values, the average of the remaining 4 groups was taken as the gram capacity and first coulombic efficiency of the batch of samples.
[0186] The parameters and effect data of each embodiment and comparative example are summarized in the following Table 1:
[0187] Table 1
[0188]
[0189] Test Example 1
[0190] The lignin-based resin of Example 1 and the lignin of Comparative Example 1 were subjected to thermogravimetric analysis using a thermogravimetric analyzer (TA TGA thermogravimetric analyzer Q50), with the temperature range set at 30°C to 1330°C and the heating rate at 1°C / min, to obtain the TGA curves of the lignin-based resin and the lignin, as shown in FIG. Figure 2 Comparing the weight loss curves of lignin and lignin-based resin, since the lignin-based resin forms a strong three-dimensional network structure after cross-linking and curing, it is more difficult to decompose and form volatile substances during heating. Therefore, at 450°C, the residual amount of lignin-based resin is 6.74% higher than that of lignin, and at 1300°C, the residual amount of lignin-based resin is 5.42% higher than that of lignin.
[0191] Test Example 2
[0192] The lignin of Comparative Example 1 and the lignin-based resin of Example 1 were cracked at 300° C., and the gas phase products were analyzed by gas chromatography-mass spectrometry (Agilent 5977B GC / MSD). The results are as follows: Figure 3A and Figure 3B As shown. Comparing the pyrolysis products of the lignin-based resin of Example 1 and the lignin of Comparative Example 1, it can be clearly seen that the pyrolysis of lignin produces a large number of small molecule aromatic compounds, such as a large number of dihydrobenzofuran (near 14.065), vinyl guaiacol (near 15.484), vanillone (near 18.981), acetosyringone (near 20.920), dibutyl phthalate (near 23.024), and oleic acid (near 24.904). However, after cross-linking and curing, the above products of the lignin-based resin are greatly reduced after pyrolysis. For example, after removing the influence of the solvent, the peak area of vinyl guaiacol decreased from 6.724% to 0.289%, the peak area of vanillone decreased from 4.847% to 1.373%, and the peak area of acetosyringone decreased from 4.092% to 0.542%, etc., and the changes were significant.
[0193] Test Example 3
[0194] The lignin-based resin of Example 1 and the lignin of Comparative Example 1 were subjected to DSC detection by using a differential scanning calorimeter (TA DSC differential scanning calorimeter Q2000), and the temperature was raised from room temperature to 250°C at 3°C / min to analyze the heat release changes of lignin and lignin-based resin during the heating process. The results are as follows: Figure 4 and 5 By comparing the DSC analysis results of the lignin-based resin in Example 1 and the lignin in Comparative Example 1, it can be seen that both the lignin and the cross-linked and cured lignin-based resin will undergo an exothermic reaction after being heated to 150°C, but the DSC heat flow curve with temperature change and the shape of the exothermic peak are quite different, indicating that there are significant changes in lignin before and after curing.
[0195] Test Example 4
[0196] The appearance of the lignin-based resin of Example 1 and the lignin of Comparative Example 1 was observed using a scanning electron microscope (TESCAN CLARA, Czech Republic). The results are as follows: Figures 6 to 9 As shown, Figure 6 and Figure 7 This is the SEM image of lignin in Comparative Example 1 of this application, Figure 8 and Fig. 9 This is a SEM image of the lignin-based resin of Example 1 of the present application. The results show that the lignin is in a spherical fusion form after extraction, while the lignin-based resin after cross-linking polymerization is blocky under an electron microscope, and the outer surface is in a layered state, which has the characteristics of a synthetic resin. The appearance structure of the two is quite different.
[0197] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.
Claims
1. A method for preparing a carbon material for a battery, wherein: The preparation method comprises the following steps: Separation: separating lignin from papermaking black liquor and drying the lignin; Polymerization: Dissolve the dried lignin in an alkaline solution, then add a cross-linking agent to carry out a cross-linking curing reaction to obtain a lignin polymer solid; Pre-oxidation: pre-oxidizing the lignin polymer solid to obtain a lignin-based resin; Pre-carbonization: pre-carbonizing the lignin-based resin under a protective atmosphere to obtain a carbon material precursor 1; Gas phase deashing: in a protective atmosphere and under the action of a halogen compound and / or a halogen element, the carbon material precursor 1 is gas phase deashed to obtain a carbon material precursor 2; Calcination: crushing the carbon material precursor and calcining it under a protective atmosphere to obtain a carbon material for a battery; Among them, the pre-oxidation temperature is 100~250℃; the pre-carbonization temperature is 300~800℃; The cross-linking agent is polyethylene glycol and formaldehyde, or polyethylene glycol, formaldehyde and hexamethylenetetramine.
2. The preparation method according to claim 1, wherein After the pre-carbonization step and before the gas phase deashing step, a washing and drying step is also included: the carbon material precursor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried.
3. The preparation method according to claim 2, wherein The pickling is carried out using any one or more acids selected from the following: sulfuric acid, hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, formic acid and acetic acid.
4. The preparation method according to claim 1 or 2, wherein: In the separation step, the papermaking black liquor is acidified with an acidifier to separate lignin from the papermaking black liquor; wherein the acidifier is selected from any one or more of carbonic acid, sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid.
5. The preparation method according to claim 4, wherein: The acidulant is selected from one, two or three of carbonic acid, sulfuric acid and hydrochloric acid.
6. The preparation method according to claim 5, wherein: The papermaking black liquor is acidified with carbonic acid to separate liquid lignin, and then the liquid lignin is acidified with sulfuric acid and / or hydrochloric acid to separate solid lignin.
7. The preparation method according to claim 6, wherein: The acidification of papermaking black liquor using carbonic acid is to reduce the pH of the papermaking black liquor to below 11 by bringing carbon dioxide into countercurrent contact with the papermaking black liquor.
8. The preparation method according to claim 7, wherein: The acidification of papermaking black liquor using carbonic acid is: using carbon dioxide to contact the papermaking black liquor with convection to reduce the pH of the papermaking black liquor to 8-10.
5.
9. The preparation method according to claim 6, wherein: The temperature for acidifying papermaking black liquor with carbonic acid is 70~200℃.
10. The preparation method according to claim 6, wherein: The temperature for acidifying papermaking black liquor with carbonic acid is 80~130℃.
11. The preparation method according to claim 6, wherein: The liquid lignin is acidified with sulfuric acid and hydrochloric acid until the pH value is less than or equal to 4.5, thereby obtaining solid lignin.
12. The preparation method according to claim 6, wherein: The liquid lignin is acidified with sulfuric acid and hydrochloric acid until the pH is 1.5-4, and solid lignin is separated.
13. The preparation method according to claim 6, wherein: The temperature for acidifying the liquid lignin with sulfuric acid and hydrochloric acid is less than 200°C.
14. The preparation method according to claim 6, wherein: The temperature for acidifying the liquid lignin with sulfuric acid and hydrochloric acid is 80-150°C.
15. The preparation method according to claim 6, wherein: The temperature for acidifying the liquid lignin with sulfuric acid and hydrochloric acid is 90-130°C.
16. The preparation method according to claim 1, wherein: The solid content of the papermaking black liquor is 8% to 70%.
17. The preparation method according to claim 1, wherein: The solid content of the papermaking black liquor is 30% to 60%.
18. The preparation method according to claim 1, wherein: In the separation step, the lignin separated from the papermaking black liquor is acid-washed or water-washed or first acid-washed and then water-washed, and then dried to obtain dried lignin.
19. The preparation method according to claim 18, wherein: In the separation step, the lignin separated from the papermaking black liquor is acid washed with any one or more acids selected from the following: sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, formic acid and acetic acid.
20. The preparation method according to claim 1, wherein: In the polymerization step, the alkaline solution is selected from one or more of sodium hydroxide solution, potassium hydroxide solution, calcium hydroxide solution and ammonia water.
21. The preparation method according to claim 1, wherein: The pH of the alkaline solution is ≥10.
22. The preparation method according to claim 1, wherein: The pH of the alkaline solution is ≥11.
23. The preparation method according to claim 1, wherein The cross-linking curing reaction temperature is 80~200℃.
24. The preparation method according to claim 1, wherein The cross-linking curing reaction temperature is 90~150℃.
25. The preparation method according to claim 1, wherein: The cross-linking curing reaction time is 1~20h.
26. The preparation method according to claim 1, wherein The cross-linking curing reaction time is 8~16h.
27. The preparation method according to claim 1, wherein The dried lignin is crushed and then dissolved in an alkaline solution.
28. The preparation method according to claim 1, wherein: The pre-oxidation temperature is 160~210℃.
29. The preparation method according to claim 1, wherein: The pre-oxidation time is 1~24h.
30. The preparation method according to claim 1, wherein: The pre-oxidation time is 4~12h.
31. The preparation method according to claim 1, wherein: The lignin polymer solid is crushed and then pre-oxidized.
32. The preparation method according to claim 1, wherein The pre-carbonization temperature is 350~700℃.
33. The preparation method according to claim 1, wherein The pre-carbonization time is 1~5h.
34. The preparation method according to claim 1, wherein The pre-carbonization time is 1~3h.
35. The preparation method according to claim 1, wherein In the pre-carbonization step, the protective atmosphere is a non-oxidizing gas atmosphere.
36. The preparation method according to claim 1, wherein The gas phase deashing temperature is 400~1500℃.
37. The preparation method according to claim 1, wherein The gas phase deashing temperature is 450~1400℃.
38. The preparation method according to claim 1, wherein The gas phase deashing temperature is 500~1300℃.
39. The preparation method according to claim 1, wherein The gas phase deashing temperature is 600~1200℃.
40. The preparation method according to claim 1, wherein The gas phase deashing temperature is 650~1150℃.
41. The preparation method according to claim 1, wherein The gas phase deashing time is 3~400min.
42. The preparation method according to claim 1, wherein The gas phase deashing time is 10~300min.
43. The preparation method according to claim 1, wherein The gas phase deashing time is 20~200min.
44. The preparation method according to claim 1, wherein In the gas phase deashing step, the protective atmosphere is an inert gas atmosphere.
45. The preparation method according to claim 44, wherein In the gas phase deashing step, the inert gas is selected from any one or more of nitrogen, helium, argon and krypton.
46. The preparation method according to claim 44, wherein In the gas phase deashing step, the inert gas is nitrogen or argon.
47. The preparation method according to claim 1, wherein The halogen element is selected from any one or more of fluorine, chlorine, bromine and iodine.
48. The preparation method according to claim 1, wherein The halogen element is chlorine gas.
49. The preparation method according to claim 1, wherein The halogen compound is selected from any one or more of the following: hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide, bromine chloride, and a compound produced by thermal decomposition and selected from any one of hydrogen fluoride, hydrogen chloride, hydrogen bromide, hydrogen iodide, chlorine fluoride, iodine chloride, iodine bromide and bromine chloride.
50. The preparation method according to claim 1, wherein The halogen compound is hydrogen chloride.
51. The preparation method according to claim 1, wherein In the gas phase deashing step, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element is 0.02~15:
100.
52. The preparation method according to claim 1, wherein In the gas phase deashing step, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element is 0.06~7:
100.
53. The preparation method according to claim 1, wherein In the gas phase deashing step, the volume ratio of the protective atmosphere to the halogen compound and / or the halogen element is 0.1~6:
100.
54. The preparation method according to claim 1, wherein In the calcining step, the carbon material precursor 2 is crushed into particles with an average particle size D50 of 1-100 μm.
55. The preparation method according to claim 1, wherein The calcination temperature is 400~2000℃.
56. The preparation method according to claim 1, wherein The calcination temperature is 500~1800℃.
57. The preparation method according to claim 1, wherein The calcination temperature is 800~1600℃.
58. The preparation method according to claim 1, wherein The calcination temperature is 1000~1500℃.
59. The preparation method according to claim 1, wherein The calcination temperature is 1100~1400℃.
60. The preparation method according to claim 1, wherein The calcination time is 0.01~20h.
61. The preparation method according to claim 1, wherein The calcination time is 0.05~15h.
62. The preparation method according to claim 1, wherein The calcination time is 0.05~10h.
63. The preparation method according to claim 1, wherein In the calcining step, the protective atmosphere is a non-oxidizing gas atmosphere.
64. The preparation method according to claim 63, wherein In the calcining step, the non-oxidizing gas is selected from any one, two or three of helium, nitrogen and argon.
65. The preparation method according to claim 1, wherein The carbon material precursor is crushed, calcined under a protective atmosphere, and further comprises a coating step: coating with pyrolytic carbon.
66. The preparation method according to claim 65, wherein The coating was carried out using chemical vapor deposition.
67. The preparation method according to claim 1, wherein The thermal weight loss rate of the lignin-based resin at 450° C. is below 42%; and the thermal weight loss rate at 1300° C. is below 72%.
68. The preparation method according to claim 67, wherein The thermal weight loss rate of the lignin-based resin at 450° C. is below 40%.
69. The preparation method according to claim 67, wherein The thermal weight loss rate of the lignin-based resin at 1300° C. is less than 70%.
70. The preparation method according to claim 1, wherein In the chromatogram obtained by pyrolysis of the lignin-based resin at 300° C. to obtain a gas phase product and then analyzing the product by gas chromatography-mass spectrometry, the peak area of vinylguaiacol accounts for less than or equal to 1%; the peak area of butylene glycol accounts for less than or equal to 2%; and the peak area of acetosyringone accounts for less than or equal to 1%.
71. The preparation method according to claim 70, wherein In the chromatogram obtained by pyrolysis of the lignin-based resin at 300° C. and analysis of the gas phase product by gas chromatography-mass spectrometry, the peak area of vinylguaiacol accounts for less than or equal to 0.5%.
72. The preparation method according to claim 70, wherein: The lignin-based resin is cracked at 300° C. to obtain a gas phase product, and in the chromatogram obtained by gas chromatography-mass spectrometry (GC-MS) chromatography analysis, the vanillone peak area accounts for less than or equal to 1.5%.
73. The preparation method according to claim 70, wherein In the chromatogram obtained by pyrolysis of the lignin-based resin at 300° C. and analysis of the gas phase product by gas chromatography-mass spectrometry, the peak area of acetosyringone accounts for less than or equal to 0.7%.
74. A carbon material for a battery prepared by the method for preparing a carbon material for a battery according to any one of claims 1 to 73.
75. The lignin-based resin obtained by the method for preparing a carbon material for a battery according to claim 1, wherein Its thermal weight loss rate at 450°C is less than 42%; Its thermal weight loss rate at 1300℃ is below 72%.
76. The lignin-based resin of claim 75, wherein Its thermal weight loss rate at 450°C is less than 40%.
77. The lignin-based resin of claim 75, wherein Its thermal weight loss rate at 1300°C is less than 70%.
78. The lignin-based resin of claim 75, wherein In the chromatogram obtained by gas phase product obtained by pyrolysis at 300°C and gas chromatography-mass spectrometry analysis, the peak area of vinylguaiacol accounts for less than or equal to 4%; the peak area of butylene glycol accounts for less than or equal to 4%; and the peak area of acetosyringone accounts for less than or equal to 3%.
79. The lignin-based resin of claim 75, wherein In the chromatogram obtained by pyrolysis of the lignin-based resin at 300° C. and analysis of the gas phase product by gas chromatography-mass spectrometry, the peak area of vinylguaiacol accounts for less than or equal to 0.5%.
80. The lignin-based resin of claim 75, wherein The lignin-based resin is cracked at 300° C. to obtain a gas phase product, and in the chromatogram obtained by gas chromatography-mass spectrometry (GC-MS) chromatography analysis, the vanillone peak area accounts for less than or equal to 1.5%.
81. The lignin-based resin of claim 75, wherein In the chromatogram obtained by pyrolysis of the lignin-based resin at 300° C. and analysis of the gas phase product by gas chromatography-mass spectrometry, the peak area of acetosyringone accounts for less than or equal to 0.7%.
82. Use of the carbon material for battery prepared by the method for preparing the carbon material for battery according to any one of claims 1 to 73 or the carbon material for battery prepared based on the lignin-based resin according to any one of claims 75 to 81 in battery hard carbon materials.
83. The use according to claim 82, wherein: The battery hard carbon material is a sodium ion battery hard carbon material or a battery hard carbon negative electrode material.
Citation Information
Patent Citations
Carbon negative electrode material of sodium ion battery
CN102701184A
Lignin-based hard carbon composite active material, preparation thereof and application of lignin-based hard carbon composite active material in sodium ion battery
CN115332521A
Preparation method and application of hard carbon negative electrode material
CN116081599A